Evaluation of three enzyme-linked immunosorbent assays for sarcoptic mange diagnosis and assessment in the Iberian ibex, Capra pyrenaica. Issue 1 (December 2016) - Ráez-Bravo, Arián; Granados, José; Serrano, Emmanuel; Dellamaria, Debora; Casais, Rosa; Rossi, Luca; Puigdemont, Anna; Cano-Manuel, Francisco; Fandos, Paulino; Pérez, Jesús; Espinosa, José; Soriguer, Ramón; et al.
Abstract Background Sarcoptic mange is a contagious skin disease caused by the miteSarcoptes scabiei, affecting different mammalian species worldwide including the Iberian ibex (Capra pyrenaica ), in which mortalities over 90 % of the population have been reported. No efficient diagnostic methods are available for this disease, particularly when there are low mite numbers and mild or no clinical signs. In this study, three enzyme-linked immunosorbent assays (ELISA) developed for dog (ELISA A), Cantabrian chamois (Rupicapra pyrenaica parva ) (ELISA B) and Alpine chamois (Rupicapra rupicapra ) (ELISA C), were evaluated to detect specific antibodies (IgG) to sarcoptic mange in Iberian ibex sera. Methods Serum samples from 131 Iberian ibexes (86 healthy and 45 scabietic) were collected from 2005 to 2012 in the Sierra Nevada Natural and National Parks (southern Spain). Based on visual inspection, ibexes were classified into one of three categories, namely healthy (without scabietic compatible lesions), mildly affected (skin lesions over less than 50 % of the body surface) and severely affected (skin lesions over more than 50 % of the body surface). The optimal cut-off point, specificity, sensitivity and the area under the curve (AUC) were calculated, and the agreement between tests was determined. Moreover, differences in the optical density (OD) related to scabies severity have been evaluated for the best test. Results ELISA C showed better performance than the two other tests, reaching higher values of sensitivity (93.0 %) and specificity (93.5 %) against the visual estimation of the percentage of affected skin, chosen as the gold standard. Significantly higher concentrations of specific antibodies were observed with this test in the mildly and severely infested ibexes than in healthy ones. Conclusions Our results revealed that ELISA C was an optimal test to diagnose sarcoptic mange in the Iberian ibex. Further studies characterizing immune response during the course of the disease, including spontaneous or drug induced recovery, should follow in order to better understand sarcoptic mange in Iberian ibex populations.